Designing A Web-Based Information System At SMP Negeri 1 Kualuh Hilir - Sinaga, Eva Rifka (Journal Of Data Science, 2024)
The rapid development of information technology in the era of globalization has brought significant changes in various fields, including education. SMP Negeri 1 Kualuh Hilir, as an educational institution, requires a web-based information system to facilitate easy and flexible access to information for students, teachers, and parents. This study aims to design and implement a web-based information system with the integration of the Internet of Things (IoT) concept for smart trash management, using the MQTT protocol and the WeMos D1 (R2) microcontroller. The research methodology includes literature studies, observations, needs analysis, hardware and software design, implementation, and system testing and evaluation. The results of the study indicate that the developed system and tools function well, with positive assessments from trials and adequate evaluation results.